1991
DOI: 10.1002/bit.260380709
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of induced CAT expression in E. coli

Abstract: The dynamics of chemically induced chloramphenicolaceyl-transferase (CAT) expression are determined in batch cultures of Escherichia coli DH5alphaF'IQ [pKK262-1]. This article is directed towards understanding the coupling of induced cloned-protein synthesis and reduced cell growth which are balanced in the optimal system. Experimental results indicate that the best inducer (IPTG) concentration is near 1.0 mM when added during midexponential growth. Lower concentrations cause only weak induction, whereas highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 33 publications
5
36
0
Order By: Relevance
“…As expected, the high induction strength resulted in higher specific CAT activity (Figure 2) for both the low and high fed-batch growth rate fermentations, although not proportionally higher. A nonproportional increase in recombinant protein expression with respect to induction strength has been observed in other E coli strains (Bentley et al, 1991;Ramirez and Bentley, 1995).…”
Section: Fed-batch Fermentationmentioning
confidence: 72%
“…As expected, the high induction strength resulted in higher specific CAT activity (Figure 2) for both the low and high fed-batch growth rate fermentations, although not proportionally higher. A nonproportional increase in recombinant protein expression with respect to induction strength has been observed in other E coli strains (Bentley et al, 1991;Ramirez and Bentley, 1995).…”
Section: Fed-batch Fermentationmentioning
confidence: 72%
“…In general it is well known that high gene expression levels in combination with high copy number plasmids can lead to reduced cell growth and viability (Bentley et al, 1991;Betenbaugh et al, 1989). In addition, there seems to be more specific problems associated with high copy number RK2 replicons (Haugan et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this equation is inappropriate when foreign protein is expressed. The metabolic burden placed on the cell during recombinant protein production has been well documented (Bentley et al, 1990;Glick, 1995) and is observed macroscopically as a reduction in growth rate (Bentley et al, 1991;Zabriskie et al, 1986). To model the mitigating effect that foreign protein expression has on the specific growth rate, the Monod expression is multiplied by a product inhibition term as follows:…”
Section: Model Developmentmentioning
confidence: 99%